2019
DOI: 10.29409/ijcmg.v12i1.283
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of cancer incidence for gender in Genetics Iraq

Abstract: There has been a rapid increase in the number of computed tomography (CT) scans which utilized for the purpose of disease diagnosis. The radiation exposure can increase the probability of developing different type of cancers. This prospective study was carried out in the Computed Tomography Unit of Al-Imamain Al-Kadhimain Medical City and Al-yarmok teaching hospital in Baghdad Iraq in the period from 1 January to 31 October2018. About 3,758 adult patients (1743 male and 2015 female) with their age ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Despite the higher incidence of TC in females, the association of gender with thyroid cancer features is still controversial. The higher estrogen and thyroid-stimulating hormone (TSH) levels, especially during pregnancy or menstrual cycle, may contribute to increase the risk of females for thyroid cancer and other cancers development such as endometrial cancer [25,26] since estrogen and TSH stimulate thyroid follicular cells to proliferate [27,28]. However, Jonklaas, et al [29] reported that both males and females represent same outcomes when getting TC at the same age [29].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the higher incidence of TC in females, the association of gender with thyroid cancer features is still controversial. The higher estrogen and thyroid-stimulating hormone (TSH) levels, especially during pregnancy or menstrual cycle, may contribute to increase the risk of females for thyroid cancer and other cancers development such as endometrial cancer [25,26] since estrogen and TSH stimulate thyroid follicular cells to proliferate [27,28]. However, Jonklaas, et al [29] reported that both males and females represent same outcomes when getting TC at the same age [29].…”
Section: Discussionmentioning
confidence: 99%